The effect of gender, energetics and biomechanics on swimming masters performance. - Ferreira, Maria (2016)
he purpose of this study was to analyze the effect of gender and energetics on biomechanics and performance of masters swimmers over 1 season. Twenty-five masters swimmers (14 male and 11 female) were assessed 3 times (TP1, TP2, and TP3) during a season (male personal record in 200-m freestyle event: 173.00 ± 31.41 seconds: female personal record in 200-m freestyle event: 200.73 ± 25.02 seconds). An incremental 5 × 200-m step test was selected to evaluate velocity at 4 mmol·l⁻¹ of blood lactate concentration (v4), maximal blood lactate concentration after exercise (La(peak)), maximal oxygen uptake (V̇O2max), stroke frequency, stroke length (SL), stroke index (SI), and propelling efficiency of the arm stroke (η(p)). The 200-m freestyle performance and average swimming velocity (v200) were also monitored. Significant differences were observed between males and females for the 200-m freestyle performance, SL, SI, and La(peak). Performance (205.18 ± 24.47 seconds; 197.45 ± 20.97 seconds; 193.45 ± 18.12 seconds), SL (1.69 ± 0.17 m; 1.79 ± 0.13 m; 1.78 ± 0.15 m), SI (1.68 ± 0.31 m²·c⁻¹·s⁻¹; 1.83 ± 0.27 m²·c⁻¹·s⁻¹; 1.85 ± 0.27 m²·c⁻¹·s⁻¹), η(p) (0.32 ± 0.04; 0.33 ± 0.03; 0.33 ± 0.04), and V̇O2max (38.71 ± 3.44 ml·kg⁻¹·min⁻¹; 43.43 ± 3.71 ml·kg⁻¹·min⁻¹; 43.95 ± 7.02 ml·kg⁻¹·min⁻¹) have changed significantly throughout the season (TP1, TP2, and TP3, respectively) in female swimmers. In male, significant changes were found in η(p) (0.33 ± 0.07; 0.36 ± 0.05; 0.36 ± 0.06) and V̇O2max (41.65 ± 7.30 ml·kg⁻¹·min⁻¹; 45.19 ± 6.55 ml·kg⁻¹·min⁻¹; 50.19 ± 9.65 ml·kg⁻¹·min⁻¹) over the season (TP1, TP2, and TP3, respectively). Gender presented a significant effect on SL (TP2: η(p)² = 0.29; TP3: η(p)² = 0.37), SI (TP2: η(p)² = 0.25), and La(peak) (TP3: η(p)² = 0.42). v4 (TP1: η(p)² = 0.23), SL (TP1: η(p)² = 0.46), SI (TP1: η(p)² = 0.78; TP2: η(p)² = 0.37; TP3: η(p)² = 0.32), and η(p) (TP1: η(p)² = 0.28) had a significant effect on performance. Male masters swimmers have better performance, SL, SI, and La(peak) than female counterparts. Female masters swimmers enhanced significantly the 200-m freestyle performance over the season due to the improvement in swimming technique (SL, SI, and η(p)) and energetic factors (v4 and V̇O2max). Nonsignificant improvements were observed for the males' performance. Gender has a significant effect on SL, SI, and La(peak). Therefore, performance is more dependent on technical factors than energetics.